Saw Sam Sai Performance - คีตโชติบัณฑิต, รชต; พันธ์รอด, มนตรี; เจริญ, นตทนันทิ; เจริญ, ศิลปะชัย (Journal of Humanities, Social Sciences, and Arts, 2022)
Saw Sam Sai is a Thai musical instrument with 3 strings using independent bow system outside the fiddle. It has been used in court ceremonies since prehistoric times. Saw Sam Sai has evidence in many academic papers and has the characteristics of the sound most similar to the singer sound. Saw Sam Sai Leep is small and high-pitched and Saw Sam Sai U is the largest in size with a low-pitched tone and still no document about the playing. The performer must be played in a manner sitting on a chair due to the length of the fiddle body. The lowest sound of the bass line is Mi and using wider trace of finger. The technique of making a heavy and slow finger creates a low-pitched vibrating sound that gives a deep and soft feeling. Combining three sizes of Saw Sam Sai shows the difference in sound characteristics and similar to the playing of the western violin family, consisting of the violin. Viola and cello (String trio). It has a complete of low, medium and high tones to complete the three fiddle strings performance in the three string fiddle band.